Church Collaboration and Resistance under Communism Revisited: The Case of Patriarch Justinian Marina (1948-1977) - Turcescu, Lucian; Stan, Lavinia (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2015)
This article revisits the history of the Romanian Orthodox Church under communism and its instrumentalization after 1989 by focusing on the figure of Patriarch Justinian Marina (1948-1977). It argues that one of his successors and protégées, Patriarch Teoctist Arăpașu (1986-2007), had an interest in repainting Marina’s relation to the communist regime as opposition, more than collaboration, because he viewed the opening of the Securitate archives in 2000 with alarm, given the large number of Securitate informers among the Orthodox clergy. It then presents a debate that has taken place in post-1989 Romania about Patriarch Justinian, and concludes that a deeper understanding of the history of ROC under early communism is possible only if Justinian is seen as both a collaborator with the regime and a defender of the ROC.